Benchmarking Comparison Of Marketing Communication Of Universities In Slovakia - Čábyová, Ľudmila; Ptačin, Jakub (Communication Today, 2025)
The authors submit the paper with the aim of introducing the benchmarking practicable in the university conditions. The paper pays special attention to theoretical definitions of benchmarking and it focuses on problems and weaknesses of marketing communication strategies applied by Slovak universities. Therefore, the main goal of the paper is to determine the most significant criteria of benchmarking comparison in the field of marketing communication implemented by selected Slovak universities. As a research result, the authors present and discuss an improvement proposal model. After carrying out a benchmark comparison applied to marketing communication at selected universities in Slovakia, they provide us with findings of the study about the use of marketing communication. Relying on the benchmarking results, they suggest recommendations for the improvement in exploitation of marketing communication in the field of higher education in the Slovak territory.